Answer:
The formula for g(x) would be [tex]g(x) = 4\sqrt{(x+3)} -3[/tex]
Step-by-step explanation:
If we let f(x)=4[tex]\sqrt{x}[/tex]
And If g(x) is the graph of f(x) which has been shifted down to 4 units and left 4 units.
What do you understand by the transformation of the graphs?
For any graph [tex]y = f(x)[/tex] we can shift the graph of [tex]y = f(x)[/tex] right h units with the addition of h to the x-axis values in the graph of [tex]f(x)[/tex].
Then the formula for g(x) would be [tex]g(x) = 4\sqrt{(x+3)} -3[/tex]
Learn more from here..............................
https://brainly.com/question/12968090
#SPJ1